Rancang Bangun Mesin Reduktor Polutan Berbasis Sirkulasi Air - Rendi Rendi; Muhammad Firman (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
Environmental pollution, especially due to pollutants, is a problem that needs special attention. One solution that can deal with this problem is to design and build a machine that can reduce pollutants. This research aims to design and build a pollutant reduction machine with a water circulation system as a reducer. This machine consists of three main components, a reducer tube, a water pump and a blower. The test is carried out by measuring the levels of carbon monoxide (CO) and hydrocarbon (HC) gas before and after passing through the reductor machine. The research results show that this machine is able to reduce carbon monoxide (CO) levels from 6.1%-6.64% to 0.98%-1.18%, and hydrocarbon (HC) levels from 714-756 ppm to 346-378 ppm. Keywords: Pollutant reduction machine, carbon monoxide (CO) levels, hydrocarbon levels (HC)